Functional Asplenia and Microscopic (Collagenous) Colitis - Hugh James Freeman (Canadian Journal of Gastroenterology)
A 54-year-old female presented with a pulmonary infection that resolved completely with antibiotic treatment. Peripheral blood films showed features characteristic of splenic hypofunction, and radiolabelling studies confirmed an absence of splenic reticulo-endothelial cell activity, which is typical of functional asplenia. The patient had a remote history of watery diarrhea but no clinical and laboratory features of malabsorption. Extensive upper and lower gastrointestinal tract biopsy studies revealed histopathological features of collagenous colitis without gastric or small intestinal inflammatory changes or epithelial lymphocytosis. Hyposplenism has been associated with different gastrointestinal disorders, particularly celiac disease. This is the first report of functional asplenia and microscopic collagenous colitis.